2021
DOI: 10.1111/josh.13023
|View full text |Cite
|
Sign up to set email alerts
|

Improved Knowledge of Disaster Preparedness in Underrepresented Secondary Students: A Quasi‐Experimental Study

Abstract: BACKGROUND: Disasters cause significant human and monetary destruction and society as a whole is underprepared to address them. Disaster preparedness education is not covered extensively enough for health professionals or for the general public. METHODS:A disaster preparedness education intervention was performed using a non-randomized controlled trial of a convenience sample with a pre-and post-intervention survey. The adapted Emergency Preparedness Information Questionnaire (EPIQ), a validated survey tool, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Drill exercises were largely highlighted in studies [ 13 , 21 – 24 ] followed by full-scale exercises [ 14 , 17 , 20 , 24 – 29 ] and tabletop exercises [ 16 , 18 , 19 ]. The other type of studies reviewed included workshop discussion-based simulation exercises [ 13 , 25 , 30 , 31 ], computer-based simulation exercise [ 32 ], and operational-based functional exercises [ 33 36 ]. The studies used different evaluation and assessment mechanisms to assess the impact and success of this simulation exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Drill exercises were largely highlighted in studies [ 13 , 21 – 24 ] followed by full-scale exercises [ 14 , 17 , 20 , 24 – 29 ] and tabletop exercises [ 16 , 18 , 19 ]. The other type of studies reviewed included workshop discussion-based simulation exercises [ 13 , 25 , 30 , 31 ], computer-based simulation exercise [ 32 ], and operational-based functional exercises [ 33 36 ]. The studies used different evaluation and assessment mechanisms to assess the impact and success of this simulation exercise.…”
Section: Resultsmentioning
confidence: 99%
“…This study found that youth and their families are impacted regularly and substantially by disasters. They report home damage, power outages, and general life disruptions, all of which can have lasting consequences on mental health (Lochman et al, 2017; Resnick et al, 2020; Self-Brown et al, 2017; White-Lewis et al, 2021). Exposure to disasters is known to be associated with a wide variety of psychological concerns in youths, such as depression, anxiety, general psychological distress, suicidal ideation, and substance abuse (O’Donohue et al, 2021; Williams et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, disaster readiness is a state in which individuals or governments have both the plan, resources, and psychological prowess needed to mitigate or offset the potential adverse effects of disasters (Su et al, 2022). Youth are important stakeholders in leading readiness for disaster events within their households and communities (White-Lewis et al, 2021).…”
mentioning
confidence: 99%
“…Kesiapsiagaan merupakan serangkaian kegiatan yang dilakukan untuk memprediksi bencana melalui suatu organisasi dan prosedur yang tepat dan efisien serta hemat biaya (Husniawati & Herawati, 2023). Pengetahuan yang ada biasanya dapat mempengaruhi sikap dan perhatian tentang kesiapsiagaan bencana sehingga harus masuk dalam kurikulum sistem pendidikan (White- Lewis, Beach, & Zegers, 2021). Bencana sulit diprediksi, membuat kesiapsiagaan bencana yang baik sangat penting untuk respons kebencanaan yang memadai (White-Lewis et al, 2021).…”
Section: Abdi: Jurnal Pengabdian Dan Pemberdayaan Masyarakatunclassified